The Reverend Mark Matthews : An Activist in the Progressive Era - Soden, Dale Edward (Book collections on Project MUSE., 2001)
"In telling Matthews's story, Dale Soden presents Matthews's multiple facets: a Southern-born, fundamentalist proponent of the Social Gospel; a national leader during the tumultuous years of schism within the American Presbyterian church; a social reformer who established day-care centers, kindergartens, night classes, and soup kitchens; a colorful figure who engaged in highly public and heated disputes with elected officials. Much of the controversy that surrounded Matthews centered on the proper relationship between church and state - an issue that is still hotly debated."--Jacket.